The Global Gotong Royong (G2R) Tetrapreneur Concept for Accelerating Tourism Village (Case Study of Karangasem Bantul Tourism Village) - Masyhari Makhasi, Ghifari Yuristiadhi; Fatimah P.L., Rika; Kenchu, Hikaru (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2025)
Not many tourist villages in Indonesia have achieved the classification of independent tourist villages (desa wisata mandiri) as stated in the Tourism Village Guidelines published by the Coordinating Ministry for Maritime Affairs and Investment of the Republic of Indonesia (2021) which oversees tourism and village affairs. Global Gotong Royong (G2R) Tetrapreneur as a sustainable entrepreneurial model concept for creating independence and authority towards global iconic products can be an acceleration towards an independent tourist village. This conceptual paper wants to offer an acceleration concept that can be carried out by the management of the Karangasem Tourism Village in Bantul Yogyakarta by implementing the four pillars of Tetrapreneur, namely Chainpreneur, Marketpreneur, Qualitypreneur, and Brandpreneur to become an independent tourist village with its global iconic product, namely bamboo crafts, which are the mainstay product of the community. The findings can also be applied to other tourist villages in Indonesia to expedite their transformation into independent tourism villages.